Strategies to reduce waiting times in outpatient rehabilitation services for adults with physical disabilities: A systematic literature review. Issue 2 (April 2022) - Dupuis, Frédérique; Déry, Julien; Lucas de Oliveira, Fabio Carlos; Pecora, Ana Tereza; Gagnon, Rose; Harding, Katherine; Camden, Chantal; Roy, Jean-Sébastien; Lettre, Josiane; Hudon, Anne; Beauséjour, Marie; Pinard, Anne-Marie; et al.
Objective: Identifying effective strategies to reduce waiting times is a crucial issue in many areas of health services. Long waiting times for rehabilitation services have been associated with numerous adverse effects in people with disabilities. The main objective of this study was to conduct a systematic literature review to assess the effectiveness of service redesign strategies to reduce waiting times in outpatient rehabilitation services for adults with physical disabilities. Methods: We conducted a systematic review, searching three databases (MEDLINE, CINAHL and EMBASE) from their inception until May 2021. We identified studies with comparative data evaluating the effect of rehabilitation services redesign strategies on reducing waiting times. The Mixed Methods Appraisal Tool was used to assess the methodological quality of the studies. A narrative synthesis was conducted. Results: Nineteen articles including various settings and populations met the selection criteria. They covered physiotherapy ( n = 11), occupational therapy ( n = 2), prosthetics ( n = 1), exercise physiology ( n = 1) and multidisciplinary ( n = 4) services. The methodological quality varied ( n = 10 high quality, n = 6 medium, n = 3 low); common flaws being missing information on the pre-redesign setting and characteristics of the populations. Seven articles assessed access processes or referral management strategies (e.g. self-referral), four focused on extending/modifying the roles of service providers (e.g. to triage) and eight changed the model of care delivery (e.g. mode of intervention). The different redesign strategies had positive effects on waiting times in outpatient rehabilitation services. Conclusions: This review highlights the positive effects of many service redesign strategies. These findings suggest that there are several effective strategies to choose from to reduce waiting times and help better respond to the needs of persons experiencing physical disabilities.